Chemical Composition, Antifungal Activity, and Plant-Protective Potential of Rosa damascena Mill. Essential Oil Against Fusarium graminearum - Özsoy, Esma; Barak, Timur Hakan; Yörük, Emre; Servi, Hüseyin; Yli-Mattila, Tapani (MDPI AG, 2025)
Fusarium graminearum is a common plant pathogen among cereals worldwide. The application of chemical antifungal compounds is the most frequently used method in controlling F. graminearum. However, its excessive use and the genomic plasticity of the fungal genome lead to increased resistance levels to these chemical antifungal compounds. In this context, plant-derived compounds might play a role in protecting against Fusarium head blight (FHB) and crown rot (CR) as an alternative. In this study, we aimed to examine the antifungal effects of an essential oil obtained from Rosa damascena Mill. on the plant pathogen F. graminearum using molecular and analytical methods. The chemical composition of the essential oil was determined by GC-MS. The half effective concentration (EC50) value of R. damascena essential oil (REO) for F. graminearum was determined as 604.25 mu g mL-1. Water-soluble tetrazolium 1 (WST-1) analyses revealed that REO caused cytotoxicity in F. graminearum. The potential oxidative stress and autophagic cell death capacity of REO towards F. graminearum was revealed via gene expression analysis and fluorescence microscopy. It was also revealed that, due to the plant-protective effect of REO, the disease severity of treated plants decreased by up to 27.78% in juvenile wheat seedlings infected by F. graminearum. Our data show that R. damascena essential oil might be used as an alternative natural ingredient in the field of plant protection.